SAT0503 SERIOUS INFECTION RISK IN PEDIATRIC PATIENTS WITH LOW IMMUNOGLOBULIN LEVELS FOLLOWING RITUXIMAB TREATMENT FOR GRANULOMATOSIS WITH POLYANGIITIS (GPA) OR MICROSCOPIC POLYANGIITIS (MPA). (13th June 2020) - Melega, S.; Brogan, P.; Cleary, G.; Hersh, A.; Kasapcopur, O.; Rangaraj, S.; Yeung, R.; Zeft, A.; Cooper, J.; Pordeli, P.; Kirchner, P.; Lehane, P.
Abstract : Background: Low immunoglobulin (Ig) levels can occur after rituximab treatment, but the clinical significance is not completely understood. Not all patients (pts) who develop low Ig levels after rituximab are at an increased risk of serious infection (SI), but factors such as pre-existing low Ig levels, prior biologic therapies, history of SI and other disease and age-related factors may increase the risk. Objectives: To assess the risk of SI in pediatric pts with prolonged low IgG or IgM serum concentrations following rituximab treatment for GPA or MPA in a global clinical trial. Methods: In the Phase 2a PePRS study (WA25615), pts aged ≥ 2 to ≤ 18 yrs with GPA or MPA received 4 weekly intravenous rituximab infusions of 375 mg/m 2 body surface area and concomitant oral glucocorticoid taper. After 6 months, pts could receive further rituximab and/or other immunosuppressants at the investigator's discretion during a minimum 12-month follow-up phase. Pts with IgG/IgM levels below age-specific reference ranges at baseline were excluded. Ig levels were measured every 4-12 wks. SI occurrence was assessed during/after low IgG or IgM. Prolonged low Ig was defined as IgG or IgM levels < lower limit of normal (LLN) reference range for age for a ≥ 4-month period. Results: All 25 pts completed 4 weekly rituximab infusions and the 6-month Remission Induction Phase; 24/25 pts completed ≥ 18 months of follow-up. 17 pts received additional rituximab treatment on or after Month 6. 11 pts received concomitant immunosuppressants (cyclophosphamide, azathioprine, mycophenolate mofetil) during the study. All pts had a decrease in IgG and IgM mostly after the first rituximab infusion. There was no consistent trend in IgG or IgM levels over time and no clear relationship between low IgG or IgM levels and the number of follow-up rituximab treatments. 18 pts (72%) had prolonged low IgG ≥ 4 months, of whom 5 had IgG levels < LLN at screening and/or baseline; in 7 pts, IgG levels returned to within normal range by study end. During or after prolonged low IgG, 6/18 pts experienced a total of 7 SIs. Three pts received treatment with intravenous Ig. 19 pts (76%) had prolonged low IgM, of whom 5 had IgM levels < LLN at screening and/or baseline. During or after prolonged low IgM levels, 6/19 pts experienced a total of 8 SIs. There were no deaths or study discontinuation due to SI. All pts with prolonged low IgG or IgM had past and/or concomitant treatment with steroids and/or immunosuppressants as potential contributory factors. Analysis of SI onset in relation to timing of low Ig was limited due to protocol-defined time points for Ig assessments. Conclusion: In pediatric pts with GPA/MPA treated with rituximab, there was no consistent pattern in IgG or IgM levels over time. The majority of pts with prolonged low IgG or IgM did not experience any SIs; no increase in the number of SIs was observed over time or with multiple rituximab treatments. While no firm conclusions can be made on a possible relationship between prolonged low IgG or IgM and risk of SI following rituximab due to study limitations (low pt numbers, lack of placebo comparator), these observations are consistent with the known rituximab safety profile in adult pts with GPA/MPA. Disclosure of Interests: Simone Melega Shareholder of: F. Hoffmann-La Roche, Employee of: F. Hoffmann-La Roche, Paul Brogan Grant/research support from: Roche, Novartis, SOBI, Chemocentryx, Novimmune, Consultant of: Roche, SOBI, UCB, Novartis, Speakers bureau: Roche, SOBI, UCB, Novartis, Gavin Cleary Speakers bureau: AbbVie, Aimee Hersh: None declared, Ozgur Kasapcopur: None declared, Satyapal Rangaraj: None declared, Rae Yeung Consultant of: AbbVie, Novartis, Speakers bureau: AbbVie, Novartis, Andrew Zeft: None declared, Jennifer Cooper Employee of: Genentech, Inc., Pooneh Pordeli Shareholder of: Roche, Employee of: Roche, Petra Kirchner Shareholder of: Roche, Employee of: Roche, Patricia Lehane Shareholder of: Roche, Employee of: Roche